Al-Kindî: On Religion And Interpretation - Müfit Selim Saruhan (Pascasarjana IAIN Metro, 2023)
The development of history and humanity opens itself up with the upper perspective obtained between different interpretations. Philosopher, Sufi, theologian, and scientist portraits are expressions that characterize prominent perpetrator personalities belonging to a field of knowledge. The main factor determining the emergence of these different nomenclatures is different interpretations in terms of the source and value of the knowledge. The position, function and method of someone who takes the mind as a reference is different, as well as the function and priorities of the researcher who adopts intuition and experience as a principle. What we are trying to emphasize here is that what distinguishes a physicist from a philosopher, a theologian or a Sufi, a Sufi from a poet or theologian lies in the source, value and functionality of knowledge. The philosopher is the personality with the most basic function in the system called philosophy. The History of Islamic Philosophy has been a system of thought that is related to every subject that philosophy is related to, to its infrastructure that influenced and its formation that influenced it afterwards. History of Islamic Philosophy tries explaining human existence, knowledge, understanding and the interpretation process as a system that tries revealing the journey of thought between cultures, languages ​​and religions. It is the humans who make all science and pursuits valuable, meaningful and valid. While trying to understand and make sense of life, the mental and sensory characteristics of human beings can reveal interpretation and new perspectives. In this article, the views of Yaqub Ibn Ishaq Al Al-Kindî on religion and the intrepratiion of religious texts will be analyzed in detail. Al-Kindî’s different philosophic methods reflect his understanding of religion. In this article, we shed light on his views about religion, language, meaning, and commentary. Al-Kindî represents an epistemological connection between religion and philosophy. He tries confirming and explain religion through pure reasoning and observation. Al-Kindî, as a philosopher, believes that religion and philosophy have specific purposes. The philosopher, who analyzes religion and philosophy in terms of the resource and purpose, obtains an upper viewpoint and can see the unity of the purpose between these two dimensions with different resources. The portrait of the philosopher represented by Al-Kindîregards texts as symbolic or encrypted and acts on the basis of their etymological meanings within the limits of language. Al-Kindî interprets the verse of the Qur’an “the same Who produces for you fire out of the green tree” (Qur’an 36/80) under the light of the principle of “contrasts are made of the contrasts” introduced in the time of Plato and Aristotle. He mentions that every being is made of something out of itself and emphasizes that every single thing has become existent out of non-existence (ex-nihilio). Al-Kindî identifies the sajdah (prostration) of celestial bodies and trees with obedience; this identification is based on his belief that there is a continuous process in nature on the basis of a cause and effect relationship set by Allah within a specific system. The obedience here must be an obligation based on the obsolete cycle in the universe.